Energy demand and heart rate evaluation at different phases during a match along an official soccer competition. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p419 - Danusa Dias Soares; João Carlos Bouzas Marins; Alexandre Sérvulo Ribeiro Hudson; Lucas Ávila Mortimer; Leonardo Gomes Coelho; Daniel Coelho; Emerson Silami-Garcia (Universidade Federal de Santa Catarina, 2012)
DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p419 The purpose of the present study was to analyze the energy expenditure and heart rate (HR), expressed as mean and maximal heart rate (HRmax), along matches of an official soccer competition. Methods: Eighteen under-20 year old (U-20) soccer players from a first-division Brazilian soccer team were evaluated during 15 matches. The relationship between HR and oxygen uptake (HR/VO2 relationship) was established, and a linear regression equation was developed for each individual player participating in the study. This equation was then used to determine the oxygen uptake and the corresponding energy expenditure based on the HR values measured during the games. The HR was recorded at 5-second intervals, which were clustered in phases of 15 minutes (0-15 min, 15-30 min e 30-45 min) for each half time (first half [FH] and second half [SH]). Results: The players' oxygen uptake was 308.3 ± 11.9 LO2/game and the energy expenditure was 17.3±1.3 Kcal.min-1 and 1,542.9±125.1 Kcal/game. The results showed that there were significant differences between the HR and HRmax identified in the first half (FH 15-30 min) compared to the second half (SH 0-15 min and SH 30-45 min), and at FH 30-45 min compared to SH 0-15 min (p<0.05). Conclusions: We concluded that soccer should be considered as an extremely arduous activity for U-20 players due to the high energy expenditure during the matches of an official championship. We also concluded that, during soccer games with young players, FH 15-30 min could be considered the most intense phase, because the highest values of HR and HRmax usually occur at this phase.